Broadband Nonlinear Optical Response in Few‐Layer Antimonene and Antimonene Quantum Dots: A Promising Optical Kerr Media with Enhanced Stability. Issue 17 (6th June 2017) - Lu, Lu; Tang, Xian; Cao, Rui; Wu, Leiming; Li, Zhongjun; Jing, Guanghui; Dong, Biqin; Lu, Shunbin; Li, Ying; Xiang, Yuanjiang; Li, Jianqing; Fan, Dianyuan; et al.
Abstract : Antimonene, a new type of 2D group‐VA material beyond phosphorene, is theoretically predicted to exhibit remarkable electronics and optical properties with enhanced stability. However, its more general and practical applications seriously lag behind due to a shortage of effective synthesis techniques in delivering high‐quality few‐layer antimonene (FLA) and antimonene quantum dots (AQDs), and deep understanding of the mechanism in light‐antimonene interaction. Herein, based on electrochemical exfoliation and sonochemical approaches, FLA is synthesized with an average thickness down to 31.6 nm and AQDs with an average lateral size of 3.4 nm, and the corresponding nonlinear optical response is further investigated at the visible wavelength for the first time. It is shown that antimonene possesses a giant nonlinear refractive index of ≈10 −5 cm 2 W −1 and a high stability in ambient condition for months. The experimental findings may be considered as an important step toward antimonene‐based nonlinear photonics devices (Optical Switcher, Kerr shutter, beam shaper, etc.), in which their unstable counterpart phosphorene may not compete with. Abstract : Based on electrochemical exfoliation and sonochemical approaches, few‐layer antimonene and antimonene quantum dots are synthesized and the corresponding nonlinear optical response is investigated at the visible wavelength. It is shown that antimonene possesses a giant nonlinear refractive index of ≈10 −5 cm 2 W −1 and a high stability in ambient condition for months.